Changes in travel behaviors and intentions during the COVID-19 pandemic and recovery period: A case study of China. (March 2023) - Fan, Xuecong; Lu, Junyu; Qiu, Miaoxi; Xiao, Xiao
Abstract: The COVID-19 pandemic severely hit the tourism industry in China and worldwide. Chinese government adopted extensive nonpharmaceutical interventions (NPIs) to control it. COVID-19 has been well under control since April 2020 and China entered into a unique recovering period. The aim of this study is to examine how the COVID-19 pandemic changed residents' travel behaviors and intentions and investigate the theoretical factors associated with these changes during the pandemic and the recovery period. This study used a mixed-methods approach by combining quantitative surveys (N = 1, 423) and qualitative interviews (N = 34). We extended the theory of planned behavior (TPB) to include other emerging factors in the context of the COVID-19 pandemic, such as risk perception, tourist trust, and charitable attitude. Our findings show that COVID-19 changed respondents' travel preferences in different ways, for example, tend to choose natural/outdoor/uncrowded attractions over cultural/indoor/crowded attractions. Second, respondents' domestic travel behaviors and intentions were positively associated with constructs in TPB, charitable attitude to contribute to the recovery of the tourism industry, tourists' trust in domestic COVID-19 control, and awareness of destinations' promotion strategies, while domestic travel intentions were negatively associated with risk perception. Third, concerns about the international COVID-19 control and travel restrictions were the two major factors affecting residents' intentions to travel abroad. Finally, we highlighted the management implications including implementing strict preventive measures while improving the effectiveness, increasing tourists' trust, and adopting diverse marketing and promotion strategies.